Implementasi Kebijakan Sistem Informasi Kearsipan Dinamis Terintegrasi (SRIKANDI) di Kecamatan Padang Utara Kota Padang - Harvi Dasnoer; Aldri Frinaldi; Lince Magriasti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The importance of using information technology as best as possible is the main goal in realizing Padang Smart Cuty, to improve services and make it easier and more concise, in today's all-digital era. Public services can only function successfully and efficiently after that. To realize good governance, the government must be able to run and utilize information and communication technology. One of the efforts to improve the quality of internal administrative services between agencies within the Padang City Government is by implementing the Integrated Dynamic Archive Information System (Srikandi) application. Srikandi aims to create smoothness in requirements and electronic filing that is effective in administering government. The research method used in writing this article is a qualitative research method. This article uses a descriptive research method with a deductive approach. The data collected are data derived from interview scripts, field notes, personal documents, memo notes and other official documents. The sample of government agencies selected in writing this article is North Padang District. The theory used in testing the implementation of the application of Srikandi is according to George C. Edward III. Based on the results of the study, it shows that the implementation of the Srikandi application in North Padang District in improving mail administration services has been implemented properly